Da‘wah and Rehabilitation: A Study of Collaborative Communication between the National Narcotics Board, Correctional Institutions, and Islamic Organizations in Addressing Narcotics Inmates - Subiantoro, Dedi; Kholil, Syukur (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2025)
This study explores the collaborative communication between the National Narcotics Board (BNN), correctional institutions, and Islamic organizations in the rehabilitation of narcotics inmates in North Sumatra. It aims to examine how inter-institutional communication systems function in the design and implementation of spiritually grounded rehabilitation programs. Using a qualitative case study approach, data were gathered through in-depth interviews, observations, and document analysis involving actors from BNN, prisons, and Islamic organizations such as Muhammadiyah, Al Washliyah, and Nahdlatul Ulama. The findings reveal that communication practices remain fragmented, relying heavily on informal relationships rather than institutionalized coordination. Nevertheless, Islamic da'wah plays a transformative role in building inmates’ moral awareness, offering empathy-based communication that complements medical and legal interventions. The study concludes that integrating religious values into formal rehabilitation systems requires strategic, systemic communication reform and recognition of Islamic organizations as equal partners.